G28(P) Developing a sustainable early life parent education programme in response to high infant mortality rates in a socio-economicall disadvantaged population. (24th May 2017) - Pillay, T; Marson, S; Porter, K; Fullwood, S
Abstract : Aims: To report on the establishment of a Parent/carer education programme aimed at addressing key risk factors for infant mortality, its uptake and impact on parents. Methods: An education programme was established, considering key risk factors/associations with infant mortality, with regional Public Health involvement. The programme rolled out after a 2 weeks intensive training of two trainers. Active parent/carer education for parents/carers whose babies were admitted onto the neonatal unit commenced since April 2016. We report on the outcomes between April 2016–September 2016. Results: Key risk factors for mortality in our region included prematurity, congenital anomalies and SIDs, with associations smoking, low birth weight, maternal age, late booking, ethnicity and social deprivation. We collated a programme incorporating achievable targets: a)Training on infant resuscitation and choking b)advice on reducing the risk of SIDS, c)smoke free homes/environment, and referral to smoking cessation teams, d)guidance on healthy weaning, e)guidance on how to recognise the poorly baby and f)support with breast feeding/other feeding choices. Families of 218 babies admitted to the NNU were offered this programme prior to discharge; 95% were mothers with partners, 6 families included grandparents in the training. Three families had experienced a previous SIDS, and 2 parents who had experienced a concurrent neonatal death (one a twin pregnancy, and another the neonatal death occurred after the training was received). Median time on the NNU was 2 days(range 0–84 days). Median maternal age was 28 years(range 15–47); 35.8% represented ethnic minorities. Programme uptake was 100%; 98.6% felt it instilled more confidence in parents/carers caring for baby at home, that practical aspects were useful, that they would recommend it to others and that it should be rolled out to all families with new babies in the region. The remaining mothers did not respond due to difficulties in written language. 11% of parents/carers admitted to smoking in pregnancy, 46% of these accepted referral to the smoking cessation team. Conclusion: the programme was well received and recommended by parents/carers. Although it is unlikely that such a programme alone can change mortality in the region, we believe that it is a step in the right direction regarding parent engagement and partnership in health care, especially in socio-economically disadvantaged areas.